2018
DOI: 10.14448/jsesd.10.0004
|View full text |Cite
|
Sign up to set email alerts
|

Implications of 3-D Printing for Teaching Geoscience Concepts to Students with Visual Impairments

Abstract: This article presents the results of a study on the use of 3-D printed models in a science classroom for students with visual impairments and examines whether the use of these models impacts student conceptual understanding and misconceptions related to geosciences concepts, specifically plate tectonics. Data were collected one week prior to instruction, one week after instruction and throughout the 3-week instructional period. Results showed that students with visual impairments held many of the same misconce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A 3D printed model is a 3-dimensional object that is made by extruding thin layers of heated plastic filament from a 3D printer to additively produce a tangible model from a drafted image (Martin et at., 2014). Tactile tools, such as braille, tactile graphics and 3D models, allow students who are blind to feel information that might otherwise be presented as a printed picture, or is too dangerous, large, small, or delicate to be touched in real life (Hasper et al, 2015;Horowitz & Schultz, 2014;Koehler et al, 2018). Since creating tactile graphics can be labor intensive, students who are blind often use descriptions of visual content to access information (Sheppard & Aldrich, 2001).…”
Section: D Printing and Its Value In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…A 3D printed model is a 3-dimensional object that is made by extruding thin layers of heated plastic filament from a 3D printer to additively produce a tangible model from a drafted image (Martin et at., 2014). Tactile tools, such as braille, tactile graphics and 3D models, allow students who are blind to feel information that might otherwise be presented as a printed picture, or is too dangerous, large, small, or delicate to be touched in real life (Hasper et al, 2015;Horowitz & Schultz, 2014;Koehler et al, 2018). Since creating tactile graphics can be labor intensive, students who are blind often use descriptions of visual content to access information (Sheppard & Aldrich, 2001).…”
Section: D Printing and Its Value In Educationmentioning
confidence: 99%
“…In a study comparing the understanding of geoscience concepts using tactile graphics and 3D printed models with students who are visually impaired, Koehler et al (2018) found the students who used 3D printed models interacted more with the tool by handling the object in different angles and rearranging the pieces, while the students using the tactile graphics only recited the content provided by the braille labels to the researcher. A study on teachers' views of tactile graphics found that students who are blind struggled to understand tactile graphics with unusual scale or perspective, like a 3-dimensional view, so teachers resorted to using models or real-life objects (Sheppard & Aldrich, 2001).…”
Section: D Printing and Its Value In Educationmentioning
confidence: 99%
“…Technology usage has been introduced with the Expanded Core Curriculum, and the use of assistive technology has been shown to be highly effective with VI students in accessing information and in the pursuit of an independent daily life (Altunay Arslantekin, 2012; Yalcin & Altunay Arslantekin, 2019). Studies in the literature support the effectiveness of assistive technology application in teaching science and mathematics since it ensures the active participation of students with VI in classes (da Mota Silveira & Martini, 2017;Koehler, Wild, & Tikkun, 2018;Ludi, Canter, Ellis, & Shrestha, 2012;Lunney, 1995;Nees & Berry, 2013;Negrete, Lisboa, Peña, Dib, & Vargas, 2020;Supalo, Humphrey, Mallouk, Wohlers, & Carlsen, 2016). Supalo et al (2016) reported that students with VI can effectively participate in technologysupported science laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Supalo et al (2016) reported that students with VI can effectively participate in technologysupported science laboratories. Similarly, Koehler et al (2018) used 3D printed models in their science class for students with VI, and indicated that adaptations in the curriculum can be effective means for teaching students with VI. However, the use of assistive technology in the education of students with VI requires comprehensive teacher training.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the same model can be used to communicate these ideas to others, including non-experts in a technical subject (Dadi et al, 2014). 3D printing is essential for commination with impaired people, especially students who require special needs for education (Kostakis et al, 2015;Jo et al, 2016;Pantazis and Priavolou, 2017;Koehler et al, 2018). In the Earth science curriculum, those students can learn common topics such as volcanoes or plate tectonics by using 3D-printed models in the classroom or at home.…”
Section: Introductionmentioning
confidence: 99%